MISSING NONVOTERS AND MISWEIGHTED SAMPLES: EXPLAINING THE 2015 GREAT BRITISH POLLING MISS. - MELLON, JONATHAN; PROSSER, CHRISTOPHER (Public Opinion Quarterly)
Preelection polls for the 2015 UK General Election missed the final result by a considerable margin: underestimating the Conservative Party and overestimating Labour. Analyzing evidence for five theories of why the polls missed using British Election Study (BES) data, we find limited evidence for systematic vote intention misreporting, late swing, systematically different preferences among "don't knows," or differential turnout of parties' supporters. By comparing the BES face-to-face probability sample and BES Internet panel, we show that the online survey's polling error is primarily caused by undersampling nonvoters, then weighting respondents to represent the general population. Consequently, demographic groups with a low probability of voting are overweighted within the voter subsample. Finally, we show that this mechanism is likely partially responsible for the polls overestimating the Liberal Democrats in 2010, illustrating that this is a longstanding problem.